Real-world experience of clinical management with antiplatelet and lipid-lowering therapy in post acute coronary syndrome patients in Indian setting - Hiremath, M; Routray, S; Shetty, Sadanand; John, John; Damle, Anil; Pradhan, Akshaya; Dharmadhikari, Aniruddha; Desai, Bhupen; Abhyankar, Mahesh; Revankar, Santosh (Heart India, 2021)
Objective: The objective is to evaluate the pattern for use of triple-drug therapy (dual antiplatelet therapy [DAPT] and statin) in the management of patients with postacute coronary syndrome (ACS) and associated risk factors in Indian settings. Materials and Methods: This was a retrospective multi-centric (n = 63), real-world, cross-sectional study which included patients (aged ≥18 years) diagnosed with an ACS, post-ACS patients from 3 months to 3 years, and receiving DAPT and lipid-lowering agents for ACS. Demographics, baseline characteristics, risk factors, medical history, and therapy details were retrieved from medical charts. Descriptive and comparative analysis for qualitative and quantitative variable was performed. Results: A total of 1548 patients with a mean age of 57.4 years were included. Male preponderance was observed across all the age groups. A total of 973 patients were on triple-drug therapy, and the most common triple fixed-dose combination prescribed was rosuvastatin, clopidogrel, and aspirin, among all the groups (age-wise: 76.1%-88.6%; sex-wise: 78.5% and 79.2%; clinical status-wise: 75.7%-81.4%). The majority of patients with non-ST-segment elevation myocardial infarction (43.0%), ST-segment elevation myocardial infarction (42.7%), and unstable angina (40.8%) received triple-drug therapy for >6 to ≤12 months duration. Adverse effect observed in patients receiving triple-drug therapy were skin rash (n = 5), bleeding (n = 2), facial puffing (n = 2), and hematuria (n = 2). A total of 357 patients were undergone switch in DAPT therapy (prasugrel to clopidogrel or ticagrelor to clopidogrel). Conclusion: DAPT and statin were the standard of care in majority of ACS patients. Triple fixed-dose combination therapy of aspirin, clopidogrel, and rosuvastatin was the most preferred choice of physicians, for optimal management post-ACS patient in Indian setting.